The Correlation of Academic Performance and Socio-Economic Background of University Students in Bangladesh - Rahmat Ullah; Ajoy Chandra; Md. Sultan Mahmud (Lafadz Jaya Publisher, 2025)
This study focuses on the relationship between students' socioeconomic backgrounds and their academic success at the university level. The goals were to identify factors influencing students' academic success and analyze the connection between socio-economic status and academic achievement. A sample of 132 participants from the University of Rajshahi was chosen through simple random sampling. Structured questionnaires were distributed to the respondents. CGPAs are used to measure academic performance. In this study, factors such as parental income, education level, occupation, students' access to resources, and learning environments are considered to evaluate overall academic success. The results reveal a significant correlation between socioeconomic status (SES) and academic achievement, with students from higher SES backgrounds often performing better due to greater access to educational resources, mentorship, and stable living conditions.